Larry Clark’s Cinéma Vérité - Amin, Faisal (Fresh Ink: Essays From Boston College’s First-Year Writing Seminar, 2011)
A look at the realism in Clark's 1995 film, Kids. The film is shot in the noninvasive style of Cinema Verite which declines to cast judgement on the controversial and morally questionable content. This essay examines the effects of this style and its addition to or detraction from realism.